Optimizing the deployment of LID facilities on a campus-scale and assessing the benefits of comprehensive control in Sponge City - Zha X.; Fang W.; Zhu W.; Wang S.; Mu Y.; Wang X.; Luo P.; Zainol M.R.R.M.A.; Zawawi M.H.; Chong K.L.; Apip A. (Elsevier B.V., 2025)
Rapid and intense urbanization has brought a wide range of serious issues like flooding and water pollution, which have become a great concern in a lot of cities. In response to these problems, Sponge City (SPC) has emerged as a potential solution. This study utilized the Stormwater Management Model (SWMM) to simulate urban runoff and determine an optimal combination of Low Impact Development (LID) strategies for reconstructing the study area. Upon analyzing the existing rainwater drainage system and revealed that it could only meet the design return period of 2-years, and identified the vulnerable flood-prone area and the maximum overflow node. After comprehensive consideration of various factors, the sponge reconstruction scenario selected four LID facilities combination: Porous pavement, Rain garden, Sunken green belt, and Green roof. Results indicated that when P = 1-yr, 5-yr, 10-yr and 20-yr, the total runoff in the LID scenario decreased by 43.91 %, 43.93 %, 45.95 % and 47.11 %, respectively. LID facilities substantially mitigate stormwater runoff and peak flows during moderate to light rainfall events. These LID facilities prove effective in reducing pollutant concentrations (reduction rate is all over 42 %), with notable reductions in Chemical Oxygen Demand (COD) and Suspended Solids (SS). This paper offers valuable insights that can serve as a reference for the construction or renovation of SPC, shedding light on effective strategies and considerations for managing stormwater and mitigating the impact of urbanization. ? 2024